Effects of city living on the mesolimbic reward system: an fMRI study - Krämer, Bernd; Diekhof, Esther K.; Gruber, Oliver (Human brain mapping, 2017)
Based on higher prevalence rates of several mental disorders for city dwellers, psychosocial stress effects of urban living have been proposed as an environmental risk factor contributing to the development of mental disorders. Recently, it was shown that amygdala activation differs between city dwellers and rural residents in response to a cognitive-social stressor. Besides its influence on the amygdala, chronic stress also affects mesocorticolimbic brain regions involved in reward processing, and stress-related dysregulation of the mesocorticolimbic dopamine system is thought to contribute to onset and manifestation of psychiatric disorders. Here, we investigated differences in reward systems functioning in 147 healthy subjects living either in cities or in less urban areas by means of functional magnetic resonance imaging during performance of the desire-reason-dilemma paradigm, which permits a targeted investigation of bottom-up activation and top-down regulation of the reward circuit. Compared with subjects from less urban areas, city dwellers showed an altered activation and modulation capability of the midbrain (VTA) dopamine system. City dwellers also revealed increased responses in other brain regions involved in reward processing and in the regulation of stress and emotions, such as amygdala, orbitofrontal, and pregenual anterior cingulate cortex. These results provide further evidence for effects of an urban environment on the mesolimbic dopamine system and the limbic system which may increase the risk to develop mental disorders. Hum Brain Mapp 38:3444-3453, 2017. © 2017 Wiley Periodicals, Inc.